Selective adsorption of bilirubin against albumin to alkylamine functionalized PVA microspheres. Issue 5 (24th March 2019) - Ma, Yingda; Chen, Jian; Li, Jian; Han, Wenyan; Chai, Yamin; Wang, Tingting; Zhang, Qian; Wang, Lichun; Wang, Weichao; Wang, Zhexiang; Ou, Lailiang
Abstract: Adsorbents are widely used in hemoperfusion for bilirubin removal. However, their performance is often compromised by the presence of plasma proteins. In this study, the bilirubin adsorption capacity of polyvinyl alcohol microspheres (PVAm) functionalized with different amino-alkane ligands has been investigated, with the aim of gaining binding selectivity over albumin. Octylamine-functionalized PVA microspheres (PVAm-8) exhibited an excellent adsorption capacity for bilirubin (75% and 3.95 mg/mL in PBS vs 72% and 3.84 mg/mL in albumin solution) when compared to the clinical adsorbent BPR (92% and 4.84 mg/mL in PBS vs 71%, and 3.80 mg/mL in albumin solution). The bilirubin adsorption capacities of PVAm-8 were largely unaffected by the presence of albumin. Adsorption of bilirubin to PVAm-8 occurs mainly through hydrophobic effects, with adsorption consistent with the monolayer model and the pseudo-first-order model operating in both PBS and albumin solution. The effects of PVAm-8 on hemolytic activity, blood component stability and coagulant activity were negligible, indicating that PVAm-8 has good potential as a high-affinity bilirubin adsorbent for hemoperfusion applications. Graphical Abstract: